Financial Devolution and Local Government: Citizen’s Perception in Azad Jammu and Kashmir - Khan, Zopash (Journal of Public Policy Practitioners, 2024)
This study aims to analyse the perception of citizens regarding accountability, competency, effectiveness, and challenges related to local government system. Respondent’s income, gender, age, familiarity with roles and responsibilities of local government members, and engagement in political discussions are important factors affecting their perception. Data has been collected through stratified random sampling. Citizens revealed that accountability and effectiveness of government will improve after financial devolution. Moreover, voters mostly preferred to cast their votes on the basis of personal affiliation. Education remains top expectation of citizens from the Local Government (LG). This study also provides policy tools for the local government policy makers.